Implementation of Risk Management for Coal Switching in Coal Fired Steam Power Plant - Fikri, Luthfi Yulian; Suparno, Suparno (Institut Teknologi Sepuluh Nopember, 2020)
Steam Power Plant is the backbone of electricity sector in Indonesia. Steam Power Plants supply 27.5 GW to the grid, in which 90% of them is coal fired. Today, several Coal Fired Steam Power Plants face a supply problem; consequently, they must procure lower quality of coal. One of them is XYZ Coal Fired Steam Power Plant. Even if there are four candidates of provider to supply coal for a minimum 10 years, it is necessary to make assessment about the effects of coal switching on equipment. The risk assessment focuses on effects of each coal sample on equipment in plant site, especially the equipment closely related to firing process, i.e., boiler, electrostatic precipitator (ESP), and Seawater Flue Gas Desulfurization (SWFGD). Risk Breakdown Structure (RBS) is employed to map problem and problem root in equipment. Risk analysis and evaluation use House of Risk (HOR), meanwhile Net Present Value (NPV) is used to evaluate financial traits. HOR analysis shows one environmental factor, i.e., emission, becomes the highest risk as each coal has high ash content; hence it is necessary to improve emission control. Three of four candidates show high NPV values suitable for the company to maximize profitability.